Comparative kinematic analysis of the leading and trailing forelimbs of horses cantering on a turf and a synthetic surface. (December 2013) - Crevier‐Denoix, N.; Falala, S.; Holden‐Douilly, L.; Camus, M.; Martino, J.; Ravary‐Plumioen, B.; Vergari, C.; Desquilbet, L.; Denoix, J.‐M.; Chateau, H.; Pourcelot, P.
Summary: Reasons for performing study: The relationship between track surface properties and limb kinematics is poorly understood. Hoof orientation within the track surface has never been quantified under training conditions. Previously described kinematic and dynamic differences between leading and trailing forelimbs at the canter poorly correlate with epidemiological data regarding injuries. Objectives: To compare joint kinematics and hoof orientation in the leading and trailing forelimbs of horses cantering on turf and on a synthetic surface. Study design: Noninvasive experimental study. Methods: The right forelimb of 5 horses was equipped with markers facing the main joints while markers and a dynamometric horseshoe were placed on the hoof. The horses were filmed with 2 high‐speed cameras (1000 Hz) while cantering (30 km/h). Recordings were repeated at each lead and alternated on turf and on a synthetic surface. Joint angles and angles of the hoof and limb to the track were measured from the 2‐dimensional coordinates of the markers. Results: Elbow, carpus and fetlock were more maximally flexed during swing and had a larger range of motion throughout the stride in the leading forelimb. Maximal carpal extension during stance was also larger on this limb, which had a more toe‐up orientation. Comparing surfaces, the limb was more oblique at landing, the range of motion of the hoof into the surface was larger, most kinematic events were delayed and fetlock and carpus extension velocities were smaller on the synthetic surface. Conclusions: The differences between limbs were more prominent than those between surfaces and the more toe‐up orientation on the hoof of the leading forelimb suggests a different loading of that limb's joints and tendons. Differences between limbs may be important in the interpretation of lead changes in lame horses. While the synthetic surface appears to be less strenuous for the joints in the forelimbs, it was associated with changes in timing of the kinematic events of the stride.